Cytotoxic and Antiproliferative Activity of LASSBio-2208 and the Attempts to Determine Its Drug Metabolism and Pharmacokinetics In Vitro Profile - Raysa Magali Pillpe-Meza; Wesley Leandro Gouveia; Gisele Barbosa; Carlos A. M. Fraga; Eliezer J. Barreiro; Lidia Moreira Lima (MDPI AG, 2024)
Inappropriate expression of histone deacetylase (HDAC-6) and deregulation of the phosphatidylinositol 3-kinase (PI3K) signalling pathway are common aberrations observed in cancers. LASSBio-2208, has been previously described as a dual inhibitor in the nanomolar range of HDAC-6 and PI3Kα and is three times more potent in inhibiting HDAC-6. In this paper we described the cytotoxic and antiproliferative potency of LASSBio-2208 on different tumour cell lines, its possible synergism effect in association with PI3K and HDAC-6 inhibitors, and its drug metabolism and pharmacokinetics (DMPK) in vitro profile. Our studies have demonstrated that LASSBio-2208 has moderate cytotoxic potency on breast cancer cell line MCF-7 (IC50 = 23 µM), human leukaemia cell line CCRF-CEM (IC50 = 8.54 µM) and T lymphoblast cell line MOLT-4 (IC50 = 7.15 µM), with no cytotoxic effect on human peripheral blood mononuclear cells (hPBMC). In addition, it has a good antiproliferative effect on MCF-7 cells (IC50 = 5.44 µM), low absorption by parallel artificial membrane permeability-gastrointestinal tract (PAMPA-GIT) and low permeation by parallel artificial membrane permeability-blood-brain barrier (BBB) (PAMPA-BBB), exhibiting high metabolic stability in rat plasma. Moreover, LASSBio-2208 exhibited synergism when combined with getadolisib and tubastatin A, using the concentrations corresponding to their CC50 values on MOLT-4 and CCRF-CEM cells.